Benchmarking of a micro gas turbine model integrated with post-combustion CO2 capture. (1st May 2017) - Ali, Usman; Font-Palma, Carolina; Nikpey Somehsaraei, Homam; Mansouri Majoumerd, Mohammad; Akram, Muhammad; Finney, Karen N.; Best, Thom; Mohd Said, Nassya B.; Assadi, Mohsen; Pourkashanian, Mohamed
Abstract: The deployment of post-combustion CO2 capture on large-scale gas-fired power plants is currently progressing, hence the integration of the power and capture plants requires a good understanding of operational requirements and limitations to support this effort. This article aims to assist research in this area, by studying a micro gas turbine (MGT) integrated with an amine-based post-combustion CO2 capture unit. Both processes were simulated using two different software tools –IPSEpro and Aspen Hysys, and validated against experimental tests. The two MGT models were benchmarked at the nominal condition, and then extended to part-loads (50 and 80 kWe ), prior to their integration with the capture plant at flue gas CO2 concentrations between 5 and 10 mol%. Further, the performance of the MGT and capture plant when gas turbine exhaust gases were recirculated was assessed. Exhaust gas recirculation increases the CO2 concentration, and reduces the exhaust gas flowrate and specific reboiler duty. The benchmarking of the two models revealed that the IPSEpro model can be easily adapted to new MGT cycle modifications since turbine temperatures and rotational speeds respond to reaching temperature limits; whilst a detailed rate-based approach for the capture plant in Hysys resulted in closely aligned simulation results with experimental data. Highlights: A microturbine is integrated with an amine-based post-combustion CO2 capture unit. The two models were benchmarked at nominal and part-loads conditions. The IPSEpro and Aspen Hysys models were extended to study exhaust gas recirculation. EGR reduces specific reboiler duty during solvent regeneration in the stripper.